Comparison of the effectiveness of self-compassion-based mindfulness package with mindfulness-based cognitive therapy package on emotional in overweight women - Hajirostam, Azam; Golparvar, Mohsen; Khayatan, Felor (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this research was to compare the effectiveness of self-compassion-based mindfulness package with mindfulness-based cognitive therapy package on emotional eating in overweight women. Method: The current research was practical and semi-experimental with a pre-test-post-test design along with a follow-up period. Among the overweight women in Isfahan who referred to weight control and weight loss centers and offices in 2019, 45 people were selected by convenience sampling and randomly assigned to the research groups. The research tool was the Van Strien et al Dutch Eating Behavior Questionnaire (1986). Each of the self-compassion-based mindfulness groups by Haji Rostam (2019) and the mindfulness-based cognitive therapy group Based on the approach of Teasdale et al (1995) underwent eight treatment sessions, and the control group did not receive any treatment. The results were analyzed using SPSS software and using variance analysis method with repeated measurements. Results: The findings showed that the mindfulness package based on self-compassion and the cognitive therapy package based on mindfulness on the desire to eat (F = 7.15, P = 0.001) and eating behavior (F = 5.74, P = 0.002) have had a lasting positive effect on overweight women. Conclusion: In this way, in order to improve the desire to eat and eating behavior in overweight women, the mindfulness package based on self-compassion and the cognitive therapy package based on mindfulness can be used.